The potential role of non-coding RNAs in acute kidney injury: a focus on natural medicine treatment - Guo, Yuxin; Zhao, Yanru; Zhang, Hanqing; Xing, Yunze; Fang, Yaxuan; Zheng, Dingyuan; Yang, Hanqi; Qiao, Yanheng; Yang, Bo (Frontiers in Molecular Biosciences, 2025)
Acute kidney injury (AKI) is a complex clinical disease characterized by sophisticated molecular pathways. Non-coding RNAs (ncRNAs), including lncRNAs, miRNAs, and circRNAs, play a pivotal role. This review focuses on the role of ncRNAs in AKI pathogenesis and their potential as biomarkers for early detection and therapeutic intervention. We carried out an extensive examination of the expression patterns, functional roles, and molecular mechanisms of lncRNAs, miRNAs, and circRNAs in AKI, as well as their relevance to treatments with natural medicines. Our findings underscore the dualistic nature of ncRNAs in AKI, acting as both protective and detrimental factors that influence key biological processes includes inflammation, oxidative stress, and apoptosis. We also point out the possible importance of other ncRNA types, such as snoRNAs and snRNAs, in AKI pathophysiology. This review provides a holistic perspective on the role of ncRNAs in AKI and lays the theoretical groundwork for the creation of innovative therapeutic strategies and biomarkers.